The creative Economy and the dynamics of regional systems: an evolutionary perspective - Christine Liefooghe (European Regional Science Association (ERSA), 2010)
In a competitive world, the creative economy seems to offer a new way of development at different scales. The flexible economy of big cities allows this diversification thanks to the agglomeration of talents in an inovative milieu and a tolerant and cosmopolitan society (Florida, 2002). This special case is becoming a model for other cities whatever the initial geographical conditions are. So the paper would like to discuss the relation between the evolution of the productive system to the creative economy and the dynamics of regional systems. We propose to test an evolutionary approach for different reasons. The first question is about the creative economy itself. Is it a new diversification of the capitalist economy, such as the "green economy" or the "digital economy" ? Or is there a new way of development thanks to the convergence between these different domains to a "creative and knowledge economy" ? So, the second question is about creativity, which is not a new concept in the research field of economy and innovation. There is a difference between creativity according to Schumpeter (1939) and its role in the business cycles, and the creative economy linked to cultural economy. So it is necessary to discuss the relation between innovation, creativity and creative economy, and to speak about the evolutionary approach of the creative economy proposed by J. Hartley (2008). Then the paper would discuss the potential trajectories of regions and cities to the creative economy model. According to research in Evolutionary Economic Geography (BOSCHMA, FRENKEN, 2005; LIU, 2009; MARTIN, 2009; NEFFKE, 2009), local and regional development depends on chance and small events, selection and lock-in processes, path dependency and increasing returns. It is a way to interprete the emergence of creative districts in former industrial quarters. But the historical and geographical context could explain why there is sometimes an evolution to a creative quarter, and sometimes not. At a regional scale, routines and institutions are crucial in the way to the creative economy, but the evolution is also the product of individual initiatives that could create, or not, a divergence into the development path.
Keywords: 330